Strategi pencegahan penangkapan ikan ilegal oleh nelayan negara asing Di Zona Ekonomi Ekslusif Indonesia - Yusuf, Haris; Zaid, Sudirman; Yusuf, Hayat (Universitas Halu Oleo, 2023)
Illegal fishing by foreign fishing boats in the Indonesian Exclusive Economic Zone is increasing every year. Along with these conditions the country suffered huge losses from this action. There is an assumption that this happened because the law enforcement authority by the Indonesian state was limited due to the provisions contained in the 1982 Convention on the Law of the Sea (UNCLOS 1982). Then when viewed from the perspective of law enforcement by the government, the handling of illegal fishing seems to be still concerning. This article examines the causes of illegal fishing activities by foreign fishermen which still occur frequently and how strategies to prevent illegal fishing by foreign fishermen in the Indonesian Exclusive Zone. The method used is a normative juridical legal research method with statuta approach and conceptual approach. The results of the study found that the causes of illegal fishing activities in Indonesian waters include limited surveillance facilities and infrastructure, limited funds for surveillance operations, limited fisheries police and Civil Servant Investigators (PPNS) and still limited ability of Indonesian fishermen to exploit their potential. fisheries in Indonesian waters. The strategies that can be taken to prevent illegal fishing are by conducting bilateral cooperation, closing access rights for fishermen from foreign countries in Indonesia's ZEE, and optimizing law enforcement in Indonesia's exclusive economic zone.